Properties and controlled release of chitosan microencapsulated limonene oil - Souza,Jefferson M. (2014)
Chitosan microcapsules containing limonene essential oil as active ingredient were prepared by coacervation using three different concentrations of NaOH (0.50, 1.00, 1.45 wt%) and fixed concentrations of chitosan and surfactant of 0.50 wt%. The produced microcapsules were fully characterized in their morphology and chemical composition, and the kinetic release analysis of the active ingredient was evaluated after deposition in a non-woven cellulose fabric. The concentration of 1.00 and 1.45 wt% clearly show the best results in terms of dimension and shape of the microcapsules as well as in the volatility results. However, at the concentration of 1 wt% a higher number of microcapsules were produced as confirmed by FTIR and EDS analysis. Free microcapsules are spherical in size with disperse diameters between 2 and 12 μm. Immobilized microcapsules showed sizes from 4 to 7 μm, a rough surface and loss of spherical shape with pore formation in the chitosan walls. SEM analysis confirms that at higher NaOH concentrations, the larger the size of the microcapsules. This technique shows that by tuning NaOH concentration it is possible to efficiently control the release rate of encapsulated active agents demonstrating great potential as insect repellent for textiles.